Morbilidad respiratoria asociada con la exposición a material particulado en el ambiente (2011)
ABSTRACT: It is assumed that prolonged exposure to airborne pollutants in the areas where people live or work can affect their respiratory systems. In order to demand for control measures aimed at protecting the community’s health, it is necessary to provide evidence for this claim. Methods: the respiratory morbidity of people living or working in urban areas of Medellín was analyzed (high particulate matter pollution. The average of PM10 is 60 µg/m3 ) and then compared with the respiratory morbidity of a matched sample of inhabitants living in the municipalities located in eastern Antioquia (low pollution. The average of PM10 is 30 µg/m3 ). Results: the groups that were compared were similar with respect to sociodemographic and other potential confounding variables. Upon comparing the two groups, a higher risk of respiratory signs and symptoms can be observed for subjects from the urban areas of Medellín. Nasal congestion, respiratory distress, and cough are the symptoms that occur in sharper contrast with relative risk of 2.60 95% CI (1.93, 3.62); 2.22 95% CI (1.56, 3.15) and 2.14 95% CI (1.63, 2.81) respectively. Conclusion: high pm10 levels as an indicator of air pollution in urban environments where people live and work contribute to a higher risk of respiratory disease. This implies adverse consequences both in economic and social terms. The control of such a situation hence becomes a social and professional priority.